2010
DOI: 10.1167/iovs.09-4955
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Basis for Bimatoprost Effects on Human Conventional Outflow

Abstract: Taken together, results suggest that bimatoprost specifically activates receptors in both cell types of the human conventional outflow pathway to modify intraocular pressure. However, only TM cell monolayers appear to have autocrine, or agonist-independent, receptor signaling that is sensitive to a prostamide receptor antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Functional prostamide receptors were found to be present in all cells involved aqueous humor outflow using cellular dielectric spectroscopy. The presence of prostamide receptors on human trabecular meshwork cells was confirmed and, in addition, such receptors were identified on the endothelial cells that line Schlemm's canal (Stamer et al, 2010). These results imply that bimatoprost influences aqueous humor drainage by interacting with both the major cell types that control pressure dependent aqueous humor outflow via the trabecular meshwork.…”
Section: B Antagonistsmentioning
confidence: 59%
See 4 more Smart Citations
“…Functional prostamide receptors were found to be present in all cells involved aqueous humor outflow using cellular dielectric spectroscopy. The presence of prostamide receptors on human trabecular meshwork cells was confirmed and, in addition, such receptors were identified on the endothelial cells that line Schlemm's canal (Stamer et al, 2010). These results imply that bimatoprost influences aqueous humor drainage by interacting with both the major cell types that control pressure dependent aqueous humor outflow via the trabecular meshwork.…”
Section: B Antagonistsmentioning
confidence: 59%
“…These results imply that bimatoprost influences aqueous humor drainage by interacting with both the major cell types that control pressure dependent aqueous humor outflow via the trabecular meshwork. Bimatoprost also increases pressureindependent aqueous humor outflow through the uveoscleral pathway (Richter et al, 2003;Woodward et al, 2010a), and functional prostamide receptors were found to be present on ciliary smooth muscle cells (Stamer et al, 2010). The effects of bimatoprost on trabecular meshwork and endothelial cells of Schlemm's canal were inhibited by the prostamide antagonist AGN 211336 (Wan et al, 2007;Stamer et al, 2010).…”
Section: B Antagonistsmentioning
confidence: 98%
See 3 more Smart Citations